Design and analysis of a cloth drying machine by using heat waste - Haziratul Najihah, Othman (2012)
This project was to study the clothes dryer machine by using heat waste. There are many cabinet dryer is widely used today as an alternative to natural clothes drying, especially for those who are busy working from morning until evening, having limited time and for the residents in urban areas. Nowadays cabinet dryer already offered in the market, but its use electrical power as a heat. Therefore in this project, heat waste will be used as an alternative to electrical heat source. The objectives of the project is to design and analyze cloth drying machine by using heat waste and to analyze performance of the drying machine. The heat waste was taken from the air conditioning. Detail drawing was developed from all concepts. In this project, Pugh Concept has been used to make evaluation of all concepts to decide final concept for further development. In order to obtain a good performance for the chosen concept, performance of drying machine using the concept has been analyzed in air flow simulation using Computational Fluid Dynamic analysis by using Solidwork Flow Simulation. The result was tested and compared with indoor natural drying and outdoor natural drying. The result from experiments show that the maximum drying rate is from the heat utilizing from air conditioning. While the result from the simulation shows that the concept B is chosen as the better performance in the simulation of the distribution of heat and,also for the airflow of temperature and velocity. As the conclusions, the concept B is chosen as the final design. The final design has been considered with all the criteria needed. Therefore, utilizing heat waste from air conditioning can be used as one of the sustainable energy resources. Anyway, future effort is required to improve the concept and to provide verification using more experimental data example like to improve the simulation by simulating the design with the cloth hanging inside the cabinet to get accurate data for better design.